Intergenerational Sexual Relationships: Are Older Men and Women Sex Predators? - Olufemi Mayowa Adetutu, Olufemi Mayowa Adetutu (African Journal of Stability and Development (AJSD), 2025)
Age-disparate sexual relationships are couched in unequal gender power dynamics, with grave social and health consequences. Older men dominate young women in sexual relationships owing to a masculine tendency. However, there is limited information on a new vista of age-disparate sexual relationships involving older women and young men. In this regard, this study explored gender and social inequalities in sexual relationships, which are largely undocumented. This study employed a qualitative research methodology to explore age-disparate sexual relationships between older men and young females, on the one hand, and young males and older women, on the other hand. Thirty (30) in-depth interviews (IDIs), six (6) focus group discussions (FGDs), and eighteen (18) key informant interviews (KIIs) were conducted across the three main ethnic groups in Nigeria. The findings showed that older men dominated young women in sexual relationships through suppression, which undermined their ability to negotiate safer sex, diminished their individual agency, and led to multiple sexual partnerships. On the other hand, participants reported that older women lured young men into sexual relationships because of financial vulnerability, sexual urges, and young men’s intentions to build contacts with the cream of society. Older men and women also preyed on their unsuspecting young victims for fetish reasons, such as ritual money and metaphysical atonement. This study showed that disadvantaged socio-economic status makes older men and women exploit and take advantage of young, unmarried women and men in sexual relationships. Wide age difference and the notion of fulfilling their side in a paid sexual intercourse make younger females and males unable to negotiate safer sex. These findings speak to gender and social inequalities in sexual relationships, which are largely undocumented in Nigeria. The study concluded that gender-based norms diminished the individual agency of emerging adults, especially females, in achieving positive sexual practices. There is a need for increased awareness of the inimical effects of age-disparate sexual relationships and transactional sex.